2005
DOI: 10.1093/gerona/60.4.491
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Death in the Nursing Home: Development and Validation of the 6-Month Minimum Data Set Mortality Risk Index

Abstract: A reasonably accurate, validated model has been produced, with clinical application through a scored point system, to assist clinicians, residents, and family members in defining good goals of care around end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 19 publications
3
70
0
6
Order By: Relevance
“…However, all available mortality prediction models have been developed using data from a single study, but all from the United States and Western Europe (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), which greatly limits their validity for use even in other high-income countries, let alone in the developing countries. For instance, a model developed using data from the Health and Retirement Study (HRS) in the United States showed poor performance when it was applied to older adults in England (18).…”
mentioning
confidence: 99%
“…However, all available mortality prediction models have been developed using data from a single study, but all from the United States and Western Europe (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), which greatly limits their validity for use even in other high-income countries, let alone in the developing countries. For instance, a model developed using data from the Health and Retirement Study (HRS) in the United States showed poor performance when it was applied to older adults in England (18).…”
mentioning
confidence: 99%
“…Predicting when residents are likely to require end of life care features in current literature on dying and has been suggested to be useful in improving the identification of dying and the initiation of specialist palliative care service provision (Grbich, Maddocks, Parker, Brown, Willis, Hofmeyer, & Piller, 2005;Mitchell, Kiely, Hamel, Park, Morris & Fries, 2004;Porock, Oliver, Zweig, Rantz, Mehr, Madsen & Petroski, 2005;Wright, Zhang, Ray, Mack, Trice, Balboni, Mitchell, Jackson, Block, Maciejewski & Prigerson, 2008). Predicting when a resident has entered a dying phase in a non malignant disease can be challenging (Miller, Teno & Mor, 2004).…”
Section: Predicting the Dying Phase In Non Malignant Diseasesmentioning
confidence: 99%
“…Predicting when a resident has entered a dying phase in a non malignant disease can be challenging (Miller, Teno & Mor, 2004). In a study of six month survival rates in nursing home residents, Porock et al (2005) calculated the risk of death using a minimum data set with a range of variables, such as gender, age, cancer, congestive heart failure, shortness of breath, treatments and activities of daily living. The purpose of the study was to identify those indicators that best predicted six month mortality and to identify those residents "who may benefit from specialist palliative care or hospice services" (p. 497).…”
Section: Predicting the Dying Phase In Non Malignant Diseasesmentioning
confidence: 99%
“…Existing models with high validity for predicting death among nursing home residents (greater than 70 percent accuracy in predicting likelihood of death in six months) have used MDS items such as diagnoses, shortness of breath, weight loss, dehydration, poor appetite, deterioration in condition, and increased number of activities of daily living requiring help. 16 Automatic eligibility is an improvement for several reasons. The six-month prognosis requirement for eligibility may limit access to hospice, particularly for the majority of nursing home residents who have terminal conditions with a less predictable life trajectory than cancer.…”
Section: Who Uses Nursing Home Hospice Services?mentioning
confidence: 99%